Assemblability design efficiency (ADE) analyses for design for automatic assemblies - Zubir @ Zubair, Baizura (2007)
The ability to quickly develop new products, which are of the lowest cost, the highest quality and the fewest environment impact, is a key factor to meet the global market demand. Design for Assembly (DfA) has been most widely applied in industries with most impressive achievements. Since the prevalence of three well known DfA tools – Boothroyd-Dewhurst DfA methodology, Hitachi Assemblability Evaluation Method (AEM) and Lucas-Hull DfA method – in industries, significant developments have been attempted in several directions not only by manual assembly but also by automatic assembly. The purpose of this project is to determine the Assemblability Design Efficiencies (ADE) by implementing the assembly analyses on the selected mechanical product for Design for Automatic Assemblies (DFAA) methodology. The results from the analyses will be used for further design improvements.